PENGARUH KESEJAHTERAAN GURU DAN KOMITMEN ORGANISASI TERHADAP KINERJA GURU PADA MTS NAHDLATUTH THULLAAB KECAMATAN LICIN - Moh. As’adi; Slamet (Jurnal Ilmu Pendidikan dan Sosial, 2023)
This research aims to; 1) find out whether teacher welfare has a partial effect on teacher performance at MTs Nahdlatuth Thullaab, Licin District; 2) find out whether organizational commitment has a partial effect on teacher performance at MTs Nahdlatuth Thullaab, Licin District; 3) find out whether the level of teacher welfare and organizational warning simultaneously influence teacher performance at MTs Nahdlatuth Thullaab, Licin District. The research method in this research is quantitative. The sampling technique uses proportional random sampling. The number of samples in this study were 30 people. Data analysis used in this research is multiple linear regression. The results of this study indicate that; 1) teacher welfare partially has a significant influence on teacher performance at MTs Nahdlatuth Thullaab, Licin District; 2) organizational commitment partially has a significant influence on teacher performance at MTs Nahdlatuth Thullaab, Licin District; 3) teacher welfare and organizational commitment simultaneously have an influence on teacher performance by 98.9% at MTs Nahdlatuth Thullaab, Licin District.